The Weapons Policy of the Canadian Forces Chaplain Branch: A Multi-Theoretical Analysis - Klein, Kevin Edward (University of Ottawa (Canada), 2009)
Military chaplains of all countries are vehemently debating the issue of chaplains bearing arms. On both sides of the debate, various arguments are advanced which get to the very nature of the chaplain's role as non-combatant and minister of religion. However, there is not a consensus between military chaplaincies or even within military chaplaincies whether or not chaplains ought to carry weapons for their own protection or the protection of others especially in the present security environment. Within the Canadian Forces chaplains are expressly forbidden from ever bearing or using personal weapons in combat operations. This thesis analyzes the question of chaplains bearing and using personal weapons from an ethical standpoint. Three ethical views will be explored: J.J.C Smart's act utilitarianism, Alasdair Macintyre's virtue ethics, and Alan Gewirth's ethical rationalism. By using these three meta-ethical perspectives, the dialogue on chaplains bearing arms within the Canadian Forces can be advanced and policies re-evaluated.
Keywords: Philosophy.